Preparation for Marriage for Muslim Women in Indonesia: Perceptions of Muslim Women in News Articles - Hastowohadi, Hastowohadi; Ramadhansyah, Ariangga; Muhammad Yusriel Amien, Muhammad Yusriel Amien (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2024)
Abstract This research explores the marriage preparation for Muslim women (Muslimah) in Indonesia by analysing perceptions found in news articles. The study focuses on understanding Muslimah’s perspectives on marriage preparation, the factors influencing their decisions, and their views on their household roles. Content analysis is employed to identify primary patterns in news articles discussing marriage preparation for Muslimah; researchers use emotional geography as an analysis tool. The research findings reveal a diversity of viewpoints, with some pieces highlighting the religious, cultural, and social aspects that influence marriage preparation. These findings can provide further insights into the demands and expectations Muslimah faces in the context of Indonesia’s marriage. The findings highlight the importance of awareness, patience, communication, individual growth, and mutual respect in fostering healthy and fulfilling connections, particularly within the context of marriage and interpersonal relationships within the Islamic framework. Keywords: Marriage; perception; online article news